The leading scientist in the field of welding steel bases.(100 Anniversary A.M. Makara) - Lyuty, O. P. (History of science and technology, 2015)
The article explores the history of the development of the technology of welding armor steels. In 1942established the world’s first technology for automatic welding tanks. Since that time, under the direction of A.M. Makara create new armor steel, their production technology and welding.